Influence of Whey Protein Isolate Supplementation on ALT and AST in Women with Polycystic Ovary Syndrome (P08-067-19). (24th October 2019) - Balcom-Luker, Shenavia; Rao, Manisha; Broughton, K Shane; LeMieux, Monique
Abstract: Objectives: The current study examined the short- and long-term effects of whey protein isolate ingestion on plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in women with polycystic ovary syndrome (PCOS). PCOS, an endocrine abnormality in women of reproductive age, is characterized by menstrual cycle disturbance, hyperandrogenism and obesity. Nutritional management options are limited. Whey protein isolate (WPI) improves metabolic parameters in patients with type 2 diabetes, but its therapeutic potential in polycystic women has yet to be realized. Women with PCOS have altered metabolic profiles and are more likely to develop liver disorders such as non-alcoholic fatty liver disease (NAFLD). Given the association between PCOS and NAFLD, we hypothesized that supplementation with WPI may attenuate circulating ALT and AST in a polycystic population. Methods: Eleven premenopausal women with PCOS and ten healthy, regularly menstruating women underwent four 150-min oral glucose tolerance tests (OGTT): (i) OGTT without protein preload, (ii) OGTT on 1st, (iii) 7th, and (iv) 60th day of protein preload. Participants consumed 35 g protein daily with protein intake 30 min before carbohydrate load on test days. Plasma levels of ALT and AST were assessed at baseline, day 1 and day 7 to determine short-term effects on liver stress using a Biolis 24i chemistry analyzer. (Participant recruitment, data collection and analyses in progress.) Results: Mixed Model Repeated Measure ANOVA indicates that time and condition (PCOS vs control) did not have a significant effect on ALT or AST levels within and between groups ( P > .05). However, preliminary data indicate that condition had a significant impact on ALT ( P < .001) and AST ( P = .001) concentrations. Changes in ALT and AST levels after 60 days of protein preload are currently being analyzed. Conclusions: Women with PCOS have higher levels of AST and ALT than those without this condition. While short-term effects of 35 g WPI ingestion do not seem to alter these levels, a longer duration of supplementation may induce more beneficial effects (currently being conducted). Findings from this study may provide foundational support for WPI as a nutritional treatment for PCOS and possible alleviation of liver stress. Funding Sources: Glanbia Nutritionals, INC, and TWU Human Nutrition Research Funds.